Burnout among nursing students: predictors and association with empathy and self-efficacy - Adriana Rezende Lopes; Oscar Kenji Nihei (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze burnout, its predictors and association with empathy and self-efficacy among nursing students. Method: cross-sectional analytical study with 284 students from five state universities in the state of Parana, Brazil. The instruments applied were: social and academic questionnaire, Maslach Burnout Inventory, Interpersonal Reactivity Index and Occupational Self-Efficacy Scale (Short Form). Spearman's correlation and univariate and multivariate logistic analysis were used. Results: 6.0% of the students presented high burnout, 36.3% presented high emotional exhaustion, 37.7% presented high depersonalization and 28.2% presented low personal accomplishment. The burnout predictors were: absence of physical activity; weekly workload >24 hours; low empathic concern. There were negative correlations between empathy (empathic concern and perspective taking) and depersonalization; self-efficacy and emotional exhaustion; and positive correlations between personal accomplishment and empathy and self-efficacy. Conclusion: Personal factors and an academic variable were burnout predictors among nursing students. The correlations suggest that self-efficacy and empathy can prevent burnout.